2007
DOI: 10.1021/om700355r
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Computational Study of the Transformation of Terminal Alkynes to Vinylidene Ligands ontrans-(Chloro)bis(phosphine)Rh Fragments and Effects of Phosphine Substituents

Abstract: Experimental and computational evidence points to unimolecular transformation of terminal alkynes on the title Rh(I) metal fragments. Lack of isotopic scrambling in double-crossover experiments is inconsistent with a previously proposed bimolecular pathway. Focusing on a unimolecular manifold, alkyne binding to the metal forms the Rh(I) alkyne π-complex 2, which isomerizes to the Rh(III) hydrido-(alkynyl) species 4, ultimately leading to Rh(I) vinylidene product 5. In making alkyne-free precursors, use of hete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 93 publications
4
52
0
Order By: Relevance
“…We have provided evidence for the profound effects of a substituent next to heterocyclic nitrogen on both chelate stability and catalytic ability [3,8,33,34,[39][40][41][42][43][44][45][46]. Ruthenium complexes 7a and 7b (Fig.…”
Section: Introductionmentioning
confidence: 84%
“…We have provided evidence for the profound effects of a substituent next to heterocyclic nitrogen on both chelate stability and catalytic ability [3,8,33,34,[39][40][41][42][43][44][45][46]. Ruthenium complexes 7a and 7b (Fig.…”
Section: Introductionmentioning
confidence: 84%
“…Ligand loss from 8 could be adjusted by selecting an appropriately labile co-ligand L, whereas chelate opening in 7 could be adjusted by varying the steric demand of R 1 next to the coordinating nitro gen, as well as by varying the sterics and electronics of the phosphine R groups. In a series of papers in the past 8 years we have provided experimental evidence for the profound role of R 1 in both chelate stability and also catalytic ability [5,[22][23][24][25][26][27][28][29][30][31][32], where a tert-butyl group often emerges as an excellent choice. For example (Fig.…”
Section: Catalyst Design Considerationsmentioning
confidence: 99%
“…Using doubly labeled alkyne H 13 C 13 CH allowed us to measure all possible C-H couplings in both the alkyne and vinylidene complexes. Previous work from our labs [27,31] showed that 1 J CC could be used much as CO infrared stretching frequencies are used to discern metal-ligand backbonding and ligand electronic effects. In the vinylidene products, within experimental uncertainty 1 J CC and 1 J CH are the same, from which we can conclude that the ligand electronics are the same.…”
Section: Anti -Markovnikov Alkyne Hydrationmentioning
confidence: 99%
“…1 These observations have been interpreted in terms of the electron-donating abilities of the basic heterocyclic phosphine substituents as well as their steric properties. 14 In recent years, an increasing amount of evidence has revealed the influence that ion pairing can have in organometallic transformations, 25 particularly in those involving proton transfer steps. Ion-pairing formation can modify the energy barrier of a proton transfer reaction by stabilization or destabilization of reaction intermediates, as shown in the kinetic study of the deprotonation of the cationic dihydrogen complex trans-[FeH(η 2 -H 2 )(dppe) 2 ] + with NEt 3 .…”
Section: ■ Introductionmentioning
confidence: 99%